Memperkuat Maritime Domain Awareness di ALKI I: Suatu Kajian Atas Kontribusi Strategis Pesawat Patroli CN-235-220 MPA - Candra Tri Wiranegara; Manahan Budiarto Pandjaitan; Moh. Qomar Syarifudin; Nitananda Prameswari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
ALKI I (Indonesian Archipelagic Sea Lane I) is one of the most strategic maritime routes within Indonesia's jurisdiction and serves as a major corridor for international maritime traffic. However, its strategic importance also makes it highly vulnerable to threats such as illegal activities, maritime law violations, and sovereignty breaches. To address these challenges, enhancing Maritime Domain Awareness (MDA) is crucial through the development of an effective and responsive maritime surveillance system. This study aims to analyze the strategic contribution of the CN-235-220 Maritime Patrol Aircraft (MPA) in strengthening MDA in the ALKI I region. Using a descriptive qualitative approach, data were collected through literature review, interviews with key stakeholders, and documentation of the aircraft's operational performance. The findings show that the CN-235-220 MPA possesses advanced capabilities in detecting, identifying, and tracking maritime activities through sophisticated sensors such as maritime radar, Automatic Identification System (AIS), and electro-optical/infrared (EO/IR) cameras. The aircraft plays a critical role in maritime surveillance operations, supports rapid response to threats, and enhances multi-agency monitoring effectiveness. Furthermore, its presence contributes to Indonesia's regional defense posture and maritime security diplomacy. The study recommends increasing the number of aircraft units, strengthening interagency system integration, and optimizing technological capabilities to sustainably enhance MDA.